Vibration type actuator, electronic apparatus, optical device and manufacturing method of vibration type actuator
By optimizing the foam member's chemical structure with a siloxane bond and specific Q/D unit ratio, the vibration actuator achieves stable and efficient performance, addressing the instability issue in existing actuators.
Patent Information
- Application Number
- JP2023096027
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-24
AI Technical Summary
Existing vibration actuators using foam members exhibit lower driving characteristics compared to those using felt, leading to instability over time.
Incorporating a foam member with a siloxane bond (Si-O-Si) and optimizing the ratio of Q units to D units (N Q /N D ≥ 0.09) in the foam structure, which includes a silicon-oxygen bond, to stabilize the driving characteristics and improve performance.
The vibration actuator maintains stable driving characteristics over a long period with improved efficiency, suitable for use in electronic and optical equipment.
Smart Images

Figure 2024177729000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a vibration actuator, an electronic device, an optical device, and a method for manufacturing a vibration actuator. [Background technology]
[0002] A vibration actuator has a vibrating body made of an electromechanical energy conversion element such as a piezoelectric element and an elastic body, and a contact body that is in pressure contact with the vibrating body. The vibration actuator is used as a vibration wave motor that moves the contact body relatively by utilizing friction generated by the driving force of vibration excited in the vibrating body.
[0003] The structure and driving principle of a vibration wave motor, which is a type of vibration actuator, are shown in outline. A vibration wave motor has a vibrating body and a contact body that is in pressure contact with the vibrating body by a biasing member. In this case, in order for the biasing member to uniformly pressurize the vibrating body, it is desirable for the rigidity of the biasing member to be increased when it comes into contact with the vibrating body. However, when a highly rigid member comes into contact with the vibrating body, it inhibits the vibration of the vibrating body, causing a deterioration in the driving characteristics of the motor. Therefore, a structure is known in which a member that does not inhibit vibration is disposed between the biasing member and the vibrating body as a vibration damping member.
[0004] Patent Document 1 lists sponge, polystyrene foam, and felt as materials for supporting the vibrating body, and discloses that wool felt is particularly excellent among them. Note that the support for the vibrating body in Patent Document 2 uses a material that does not inhibit vibration, and is considered to have the same function as a vibration damping material.
[0005] Patent document 2 also describes a vibration actuator in which a foamed material is disposed between a vibrating body and a biasing member, and by selecting the average circular equivalent diameter of the cells of the foamed material, stable and sufficient output can be obtained over a long period of time. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 3-289371 [Patent Document 2] JP 2022-83146 A Summary of the Invention [Problem to be solved by the invention]
[0007] Here, in a vibration type actuator using a foam member, the driving characteristics may be degraded compared to when felt is used.
[0008] The present invention has been made to address the above-mentioned problems, and provides a vibration actuator having stable driving characteristics over a long period of time and improved driving characteristics.The present invention also provides electronic devices and optical devices using a vibration actuator having stable driving characteristics over a long period of time and improved driving characteristics.The present invention also provides a manufacturing method for a vibration actuator having stable driving characteristics over a long period of time and improved driving characteristics. [Means for solving the problem]
[0009] The vibration actuator of the present invention includes a vibrating body having an elastic body including an electromechanical energy conversion element and a plate portion and a protrusion portion protruding in the same direction outside the surface of the plate portion, a contact portion that contacts the protrusion portion of the vibrating body and moves relatively to the vibrating body, a foam member that contacts the vibrating body, and a biasing member that biases the vibrating body against the contact portion via the foam member, the foam member containing a siloxane bond (Si-O-Si) consisting of silicon and oxygen, and the number N of silicon units Q contained in the foam member is Q Number of D units in N D Ratio to N Q / N D is 0.09 or more. Effect of the Invention
[0010] According to the present invention, it is possible to provide a vibration actuator having stable driving characteristics over a long period of time and improved driving characteristics.Furthermore, according to the present invention, it is possible to provide electronic devices and optical devices using a vibration actuator having stable driving characteristics over a long period of time and improved driving characteristics.Furthermore, according to the present invention, it is possible to provide a manufacturing method for a vibration actuator having stable driving characteristics over a long period of time and improved driving characteristics. [Brief description of the drawings]
[0011] [Figure 1] 1A and 1B are diagrams illustrating a schematic structure of a vibration actuator of the present invention using a circular or rectangular piezoelectric material. [Diagram 2] 1A and 1B are diagrams illustrating two vibration modes generated by a vibrator of the present invention having a rectangular piezoelectric material. [Diagram 3] FIG. 2 is a schematic cross-sectional view illustrating a foam member according to the present invention. [Figure 4] FIG. 2 is a schematic side view of a foam member according to the present invention. [Diagram 5] FIG. 2 is a diagram illustrating a structural unit that constitutes the backbone structure of a molecule containing a siloxane bond. [Figure 6] 2 is a 29Si-DD-MAS NMR spectrum obtained by solid-state NMR of a foamed member of the present invention. [Figure 7] FIG. 7 is a diagram showing molecular structures assigned to each peak in FIG. 6. [Figure 8] 1 is a diagram illustrating a schematic structure of an optical device according to the present invention. [Figure 9] FIG. 4 is a diagram showing the driving characteristics of a vibration actuator according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described.
[0013] The present inventors discovered that a vibration actuator using a foamed material has poorer drive characteristics than one using felt. As a result of further investigation, the present inventors discovered that by optimizing the chemical structure of the foamed material, a vibration actuator having stable drive characteristics over a long period of time and improved drive characteristics can be obtained.
[0014] The vibration actuator of the present invention has a vibrating body, a contact body, a foam member, and a biasing member. The vibration actuator of the present invention has a foam member that contains a siloxane bond (Si-O-Si) and has a number N of Q units. Q Number of D units in N D Ratio to N Q / N D Since the foam material contains a large number of Q units, the effect of stabilizing the siloxane structure is obtained, and it is possible to obtain a vibration actuator whose driving characteristics are not easily deteriorated even when used for a long period of time.
[0015] The schematic structure of the vibration actuator of the present invention is illustrated in Fig. 1 and Fig. 2. Fig. 1 (a) and (d) are side views showing the schematic diagram of the vibration actuator, (b) and (e) are perspective views, and (c) and (f) are rear views. Fig. 2 (a) is a diagram explaining the vibration mode A, and (b) is a diagram explaining the vibration mode B.
[0016] 1 and 2 use a vibrating body with a circular plate portion and a vibrating body with a rectangular plate portion, respectively. The vibration actuator 100 of the present invention includes an electromechanical energy conversion element 120 made of an electrode 101 and a piezoelectric material 102. It further includes an elastic body 103 having a plate portion 108 and a protrusion portion 106 protruding in the same direction outside the surface of the plate portion, and these are arranged in order to form a vibrating body 110.
[0017] The vibration actuator 100 further includes a contact body 104 that contacts the protrusion 106. In addition, a biasing member 121 for pressurizing the vibration body 110 into contact with (biases) the contact body 104, and a foam member 122 is provided between the vibration body 110 and the biasing member 121.
[0018] When the vibrating body 110 is driven, the vibrating body 110 and the contact body 104 move relatively. The contact body 104 is not limited to being in direct contact with the vibrator 110 as long as it is a member that can move relatively to the vibrating body 110, and may be in indirect contact with the vibrating body 110 via another member. The surface of the electromechanical energy conversion element 120 is urged toward the contact body 104 by the urging member 121 via the foam member 122.
[0019] (Piezoelectric materials) The shape of the piezoelectric material 102 is not important, but if the plate portion is shaped like a ring, the piezoelectric material is preferably also shaped like a ring, and if the plate portion is shaped like a rectangle, the piezoelectric material is preferably also shaped like a rectangle.
[0020] The form of the piezoelectric material 102 is not limited, but may be, for example, a piezoelectric material (sintered body) without crystal orientation, crystal-oriented ceramics, piezoelectric single crystal, etc. The shape that the piezoelectric material can take is not limited, but for example, a layered piezoelectric material may be adopted to form a laminate of electrodes and piezoelectric material, or a single plate of piezoelectric material may be adopted. From the viewpoint of the cost of the piezoelectric material, a single plate is superior. In order to drive a vibration type actuator, a polarization process is performed on the piezoelectric material. When the AC electric field frequency applied to the polarization-processed piezoelectric material approaches the resonant frequency of the piezoelectric material, the piezoelectric material vibrates greatly due to the resonance phenomenon.
[0021] From the viewpoint of environmental load, the lead content of the piezoelectric material used in the electromechanical energy conversion element is preferably 1000 ppm or less.
[0022] (electrode) When a circular toric piezoelectric material is used, electrodes 101 divided in the circumferential direction are provided on the piezoelectric material to form a circular toric piezoelectric element. The electrodes 101 consist of a driving phase electrode 101e and a non-driving phase electrode 101f. The circumferential length of the driving phase electrode is 1 / 2 the wavelength λ of the vibration wave generated in the circumferential direction of the circular toric piezoelectric element when an alternating voltage is applied to the driving phase electrode. The circumferential length of the non-driving phase electrode (ground electrode, monitor electrode) is 1 / 4 of the wavelength λ. The number of driving phase electrodes and non-driving phase electrodes varies depending on the number of traveling waves excited in the circular toric piezoelectric material. The piezoelectric material corresponding to each driving phase electrode is polarized with a voltage of a different polarity from that of the adjacent regions.
[0023] The driving phase electrodes are separated by an odd number of non-driving phase electrodes. After polarization processing, a first electrode 101a and a second electrode 101b are provided to short-circuit the two driving phase electrode groups separated by the non-driving phase electrodes. The first electrode 101a and the second electrode 101b are used to drive a vibration type actuator using a circular annular piezoelectric material.
[0024] When a rectangular piezoelectric material is used, a rectangular electrode 101 is provided. The electrode 101 is composed of a first electrode 101a and a second electrode 101b. The first electrode 101a and the second electrode 101b are used for polarization processing of the rectangular piezoelectric material and for driving a vibration type actuator using the rectangular piezoelectric material.
[0025] The electrodes are made of a metal film with a thickness of about 0.3 to 10 μm. The material is not particularly limited, but silver, gold, or platinum electrodes are generally used. The method for manufacturing the electrodes is not limited, and they can be formed by screen printing, sputtering, vacuum deposition, or the like. In order to manufacture an electromechanical energy conversion element with a lead content of 1000 ppm or less, it is necessary to use a paste or target with a lead content of less than 1000 ppm in forming the electrodes.
[0026] (Elastic body) From the viewpoint of the properties as an elastic body and workability, it is preferable that the elastic body 103 is made of a metal. Examples of metals that can be used for the elastic body 103 include aluminum, brass, and stainless steel. Among stainless steels, martensitic stainless steel is preferable, and SUS420J2 is most preferable. The elastic body has a protrusion 106 that contacts the contact body. To further improve the wear resistance of the protrusion, the elastic body is subjected to quenching, plating, or nitriding.
[0027] It is preferable that the plate portion of the elastic body is rectangular. By making the plate portion of the elastic body rectangular, the manufacturing process of the electromechanical energy conversion element becomes easier, and a small electromechanical energy conversion element can be produced. As a result, it becomes possible to produce a small vibration type actuator.
[0028] (Foam material) 1(a), the foam member 122 is provided on the surface of the electromechanical energy conversion element 120 opposite to the surface on which the elastic body 103 is provided. The foam member 122 uniformly presses the vibrating body 110 against the contact body 104 and is also required to function as a vibration damping member. The function of the foam member 122 as a vibration damping member is to dampen vibrations from adjacent members by absorbing or the like, and the foam member 122 may be provided separately as long as the driving characteristics are not deteriorated.
[0029] Fig. 3 shows a horizontal cross-sectional view (XY plane) of a foamed material of the present invention, and Fig. 4 shows a vertical side view (Z direction) of the foamed material of the present invention. Fig. 4(a) shows a side view of a foamed material without a skin layer on the surface, and Fig. 4(b) shows a side view of a foamed material with a skin layer on the surface.
[0030] The foam member 122 contains a siloxane bond (Si-O-Si) consisting of silicon and oxygen, and the number N of Q units of silicon contained in the foam member Q Number of D units in N D Ratio to N Q / N DThe foam material is characterized by having a refractive index of 0.09 or more. By containing a siloxane bond (Si-O-Si) consisting of silicon and oxygen, the glass transition temperature of the foam material can be made lower than the operating temperature range of -30°C, and the physical properties of the foam material can be maintained at low temperatures equivalent to those at room temperature.
[0031] The number of silicon Q units contained in the foam material is N Q Number of D units in N D Ratio to N Q / N D By making the value of the skeletal structure larger than 0.09, it is possible to improve the driving efficiency of the vibration type actuator. Here, the Q and D units of silicon refer to the units that constitute the skeleton structure of a molecule containing a siloxane bond. As shown in Fig. 5, (a) a monofunctional unit with three organic substituents is called an M unit, (b) a bifunctional unit with two organic substituents is called a D unit, (c) a trifunctional unit with one organic substituent is called a T unit, and (d) a tetrafunctional unit with no organic substituents is called a Q unit. The M units refer to both ends of the skeleton structure. The D units show flexibility in the skeleton structure, while the T and Q units show rigidity in the skeleton structure.
[0032] In a foamed material, the number of Q units of silicon contained in the foamed material, N Q Number of D units in N D Ratio to N Q / N D When the ratio N is 0.09 or more, the material is suitable as a vibration damping member, and the driving efficiency of the vibration actuator can be improved. Q / N D If the foamed member is too flexible, and the pressure applied to the vibrator by the biasing member becomes non-uniform, this is not preferable because it may result in large variations in characteristics and reduced drive efficiency.
[0033] Although T units may be present to harden the skeletal structure, it is preferable that the ratio of Q units is greater than that of T units in order to maintain the structural hardness of the skeletal structure and make it stable over a long period of time. On the other hand, if the skeletal structure is too hard, it will inhibit the vibration of the vibrating body, which will cause deterioration of the driving characteristics of the motor and generate abnormal noise. Preferably, the number N of silicon Q units contained in the foamed material is Q Number of D units in N D Ratio to N Q / N D is 0.5 or less, and more preferably 0.29 or less.
[0034] The structural units of silicon compounds contained in foamed materials can be identified by molecular structure analysis using solid-state nuclear magnetic resonance (hereinafter referred to as solid-state NMR), and the proportion of the structural units can be calculated. The NMR method is a method for measuring the excitation energy of nuclear spins, and in the case of silicon compounds, 29 By observing the Si nuclei, it is possible to obtain information about the molecular structure.
[0035] In addition, there are two methods for measuring silicon compounds using solid-state NMR: the DD (Dipolar Decoupling) method and the CP (Cross Polarization) method. The CP method is used to measure the crystallinity and 1 The detection sensitivity varies greatly depending on the presence of H. Therefore, the integral ratio of the measurement signal cannot accurately reflect the ratio of each component. On the other hand, the DD method has a lower sensitivity than the CP method and requires a long measurement time, but by optimizing the measurement time, the ratio of each component can be calculated from the integral ratio of the measurement signal. The DD method must be used to calculate the structural units of the silicon compound contained in the foamed material of the present invention.
[0036] FIG. 6(a) shows the solid-state NMR data of the foamed material in the vibration actuator of the present invention. 29An example of a Si-DD-MAS NMR spectrum is shown in Fig. 6(b), which is an enlarged view of the area enclosed by the dotted line in Fig. 6(a). The horizontal axis of the NMR spectrum is called the chemical shift value δ (ppm), which is the deviation from the reference resonance frequency divided by the reference frequency, and indicates a unique value for each structure.
[0037] For example, the structure of Q4 in Figure 6(b) can be identified from the presence of a peak in the NMR spectrum at -110 ppm. The SSB in Figures 6(a) and (b) stands for spinning side band, which is a ghost signal detected due to the anisotropy of the molecular structure. The molecular structures assigned to each peak in Figures 6(a) and (b) are shown in Figure 7. Although they can be assigned to various molecular structures depending on the element and type of molecule bonded to the central Si, in this invention, they are classified into four types, M unit, D unit, T unit, and Q unit, and the ratio is calculated. In other words, in the molecular structure in Figure 7, M0 and M0 H in M units, D2 and D2 H The peak area intensity is calculated using D unit, T1 and T2 in T unit, and Q3 and Q4 in Q unit.
[0038] In the NMR spectrum, the M unit peak can be seen in the range of 20 ppm to 0 ppm, the D unit peak can be seen in the range of 0 ppm to -45 ppm, the T unit peak can be seen in the range of -45 ppm to -85 ppm, and the D unit peak can be seen in the range of -85 ppm to -120 ppm.
[0039] The structural units of silicon Q and D units represent crosslinking points, and their ratio indicates the crosslinking point density. In the foaming process, the crosslinking point density and the average circle equivalent diameter of the bubbles can be changed by controlling the heating temperature and time in the curing by heat curing or crosslinking reaction caused by mixing two liquid raw materials. For a foaming material containing silicone resin with an average circle equivalent diameter of bubbles larger than 120 μm, 2 More than 700g / cm 2 A foamed material was obtained by heat treatment at a temperature of 60° C. to 80° C. under the following pressure. It is considered that the structure of the foamed material is stabilized by performing the pressurized heat treatment, and this is preferable.
[0040] The foamed material is preferably a sponge containing silicone rubber. Similar effects can also be obtained by substituting some of the methyl groups of the silicone rubber with vinyl groups or phenyl groups. Silicone sponges are preferred because they have smaller volumetric changes in the thickness direction under pressure than felt, and have excellent long-term stability. For example, felt with a pressure of 600 g / cm at room temperature 2 More than 700g / cm 2 When held under the following pressure for 500 hours, the thickness is compressed to about 50% and does not return to its original state even when the pressure is released. On the other hand, silicone sponge returns to almost its original thickness when the pressure is released, so the change in volume is small.
[0041] The foamed material is characterized in that the average equivalent circular diameter of the bubbles contained therein is greater than 120 μm. The average equivalent circular diameter of the bubbles contained in foamed material 122 is preferably greater than 120 μm. The presence of bubbles in the foamed material allows the foamed material to have spring properties, and the foamed material can uniformly pressurize vibrating body 110 against contact body 104 and function as a vibration damping member.
[0042] The average equivalent circular diameter is preferably calculated from the cross-sectional shape of the foamed material. When the average equivalent circular diameter of the bubbles in the cross section of the foamed material is greater than 120 μm, it is possible to uniformly pressurize the vibrating body while maintaining the driving characteristics of the motor without impeding the vibration of the vibrating body.
[0043] The average circular equivalent diameter of the foamed member 122 can be obtained by a method such as image processing of a cross-sectional image obtained by cross-sectional observation. In order to perform cross-sectional observation, a sample may be cut to expose the cross-section and observed with an optical microscope or a laser microscope. Another method is to obtain a non-destructive cross-sectional image by X-ray CT scanning. If it is possible to confirm the shape of the bubbles, the surface in contact with the electro-mechanical energy conversion element 120 may be treated as the cross-sectional shape. Image processing software may be optimized for a microscope or may be commercially available. Since bubbles of various sizes exist, it is preferable to observe many bubbles when calculating the average circular equivalent diameter. Specifically, it is preferable to calculate the average circular equivalent diameter from 50 or more bubbles.
[0044] The foamed material of the present invention may have columnar cells as shown in Fig. 4(b), or may have a skin layer on the surface of the foamed material. As shown in Fig. 4(b), when a skin layer is present on the surface, the bubbles cannot be accurately confirmed from the surface, so it is preferable to expose the cross section by cutting. The average equivalent circle diameter can be calculated from the obtained cross-sectional photograph by image processing.
[0045] It is preferable that the bubbles in the foamed material are mainly composed of closed bubbles. Closed bubbles refer to bubbles that are not connected to the front and back of the foamed material by bubbles. Closed bubbles are difficult to pass gas or liquid through. For this reason, closed bubbles are preferable for the foamed material to have spring properties. On the other hand, open bubbles have the characteristic that air is easily allowed to enter and exit because the bubbles are connected, and they are easily crushed when pressure is applied, and are undesirable because they have poor spring properties, so there is a risk that the vibrator cannot be pressurized uniformly and the vibration damping function is reduced. It is preferable that the number of closed bubbles is greater than the number of connected bubbles, that is, the number of closed bubbles accounts for 50% or more of the number of bubbles contained in the foamed material. In this case, the number can be counted from a cross-sectional photograph containing 50 or more bubbles.
[0046] It is more preferable that the average equivalent circular diameter of the bubbles of the foamed material is 200 μm or more. In order to realize stable operation within the operating temperature range of the vibration actuator (for example, -30°C to 60°C), it is effective to use a piezoelectric material with a phase transition temperature of -10°C or less for the vibration actuator. In other words, it is effective to use a piezoelectric material whose piezoelectric properties at -10°C are greater than those at room temperature for the vibration actuator. In this case, by making the average equivalent circular diameter of the bubbles 200 μm or more, it is possible to maintain the effect as a vibration damping member in the low temperature range and improve the driving efficiency. It is more preferable that the average equivalent circular diameter of the bubbles is 300 μm or more.
[0047] The average equivalent circular diameter of the foamed member is preferably smaller than 1 / 2 the thickness t of the foamed member. This allows the vibrator to be uniformly pressurized and the foamed member to function as a vibration damping member. More preferably, the foamed member has an average equivalent circular diameter smaller than 1 / 3 the thickness t of the foamed member.
[0048] (contact body) From the viewpoint of rigidity, the contact body 104 is preferably made of stainless steel. Among stainless steels, martensitic stainless steel is preferable, and SUS420J2 is most preferable. The contact body 104 must have excellent wear resistance because it is in frictional contact with the elastic body 103, and its surface is subjected to nitriding or anodizing. A frictional force is generated between the protrusion 106 and the contact body 104 due to the pressurized contact. The tip of the protrusion 106 vibrates elliptically due to the vibration generated by the electromechanical energy conversion element 120, and a driving force (thrust) for driving the contact body 104 can be generated. The contact body is generally called a slider or rotor.
[0049] The "contact body" refers to a member that comes into contact with the vibrating body and moves relative to the vibrating body due to vibrations generated in the vibrating body. The contact between the contact body and the vibrating body is not limited to direct contact with no other member interposed between the contact body and the vibrating body. The contact between the contact body and the vibrating body may be indirect contact with another member interposed between the contact body and the vibrating body, as long as the contact body moves relative to the vibrating body due to vibrations generated in the vibrating body. The "other member" is not limited to a member independent of the contact body and the vibrating body (e.g., a high-friction material made of a sintered body). The "other member" may be a surface-treated portion formed on the contact body or the vibrating body by plating, nitriding, or the like.
[0050] (Piezoelectric vibrator) In the annular piezoelectric element, the piezoelectric material in contact with the adjacent driving phase electrodes is polarized with different polarities, so when an electric field of the same polarity is applied to the driving phase electrode 101e, the expansion and contraction polarity in the corresponding region of the piezoelectric material alternates at a pitch of λ / 2. When an alternating voltage is applied to the first electrode 101a, a first standing wave with a wavelength of λ is generated over the entire circumference of the vibrator. When an alternating voltage is applied to the second electrode 101b, a second standing wave is generated in the same manner, but the position of the wave is rotated by λ / 4 in the circumferential direction relative to the first standing wave. On the other hand, when two types of alternating voltages with the same frequency and a temporal phase difference of π / 2 are applied to the first and second electrodes, the following traveling wave is generated. That is, as a result of the synthesis of the first and second standing waves, a traveling wave (wave number n along the annulus, wavelength λ) of bending vibration (vibration whose amplitude is perpendicular to the surface of the vibrator) that travels in the circumferential direction over the entire circumference is generated in the vibrator.
[0051] When a traveling wave of bending vibration (hereinafter sometimes simply referred to as "bending vibration wave") is generated, each point on the surface of the diaphragm that constitutes the vibrator moves elliptically, so that a moving body in contact with this surface receives a circumferential frictional force (driving force) from the diaphragm and rotates. The direction of rotation can be reversed by switching the positive and negative phase difference of the alternating voltage applied to the first and second electrodes. The rotation speed can also be controlled by the frequency and amplitude of the alternating voltage applied to the first and second electrodes.
[0052] 2 illustrates two vibration modes generated by a vibrator of the present invention having a rectangular piezoelectric material. The rectangular piezoelectric material is provided with a first electrode 101a and a second electrode 101b, and the respective regions are referred to as a first region and a second region.
[0053] Mode A When both the first region and the second region expand or contract, a first bending vibration mode (mode A) is generated. Mode A is excited most strongly when the phase difference between the alternating voltages VA and VB applied to the first electrode 101a and the second electrode 101b is 0° and the frequency is near the resonant frequency of mode A. Mode A is a primary out-of-plane vibration mode in which two nodes (where the amplitude is minimum) appear approximately parallel to the long side of the vibrator 110. Two protrusions 106 protruding in the same direction in the elastic body are disposed near positions that become antinodes (where the amplitude is maximum) of mode A. Therefore, the tip surfaces of the protrusions 106 reciprocate in the Z direction due to vibration mode A.
[0054] Mode B When the first region expands and contracts, the second region contracts and expands, respectively, and a second bending vibration mode (mode B) is generated. Mode B is excited most strongly when the phase difference between the alternating voltages VA and VB applied to the first electrode 101a and the second electrode 101b is 180° and the frequency is near the resonance frequency of mode B. Mode B is a secondary out-of-plane vibration mode in which three nodes appear approximately parallel to the short sides of the vibrator 110. The protrusion 106 of the elastic body is disposed near the node position of mode B. Therefore, the tip surface of the protrusion 106 reciprocates in the X direction by mode B.
[0055] In the vibration actuator 100, when the phase difference between the alternating voltages VA and VB is 0 to ±180°, mode A and mode B are excited simultaneously, and elliptical vibration is excited in the protrusion 106 of the elastic body. A vibration actuator that uses a rectangular piezoelectric material and is driven by mode A and mode B is preferable because it can be easily miniaturized.
[0056] It is more preferable that there are two protrusions protruding in the same direction outside the plane of the plate. This is preferable because it is easy to miniaturize the vibration actuator that uses rectangular piezoelectric material and is driven by mode A and mode B as shown in Figure 2.
[0057] In order to prevent vibration inhibition due to deformation of the foam member caused by pressurization, it is preferable that the area of the contact portion between the foam member and the electro-mechanical energy conversion element is smaller than the area of the planar portion of the electro-mechanical energy conversion element including the above portion. In addition, it is preferable that the foam member is smaller than the electro-mechanical energy conversion element. It is expected that the foam member can be expected to suppress problems such as the foam member deforming and wrapping around the side of the foam member and the piezoelectric element, which is the electro-mechanical energy conversion element, inhibiting the vibration of the piezoelectric element, or interfering with surrounding members, inhibiting the vibration. In addition, it is preferable that the foam member is smaller than the elastic body. If the foam member is larger than the elastic body, it may deform and interfere with surrounding members, inhibiting the vibration, so it is expected that the foam member can be expected to suppress problems such as the foam member being smaller than the elastic body.
[0058] (Composition of piezoelectric material) The composition of the piezoelectric material 102 is not particularly limited as long as it can be used as a vibration type actuator.
[0059] Generally, lead zirconate titanate (PZT)-based materials are used for piezoelectric materials. However, in light of the recent concern over the impact of lead on the environment, it is more preferable to use a piezoelectric material that uses a perovskite-type metal oxide that does not contain lead (lead content is less than 1000 ppm). The lead content can be measured, for example, by ICP atomic emission spectrometry.
[0060] It is more preferable that the piezoelectric material does not contain lead, that is, is lead-free, and the main component thereof is a barium titanate-based material.
[0061] The piezoelectric material is preferably made of a barium titanate-based material, from the viewpoint of high piezoelectric constant and relatively easy manufacturing. Here, examples of barium titanate-based materials include barium titanate (BaTiO3), barium calcium titanate ((Ba,Ca)TiO3), barium zirconate titanate (Ba(Ti,Zr)O3), and barium calcium zirconate titanate ((Ba,Ca)(Ti,Zr)O3). Other examples include compositions such as sodium niobate-barium titanate (NaNbO3-BaTiO3), sodium bismuth titanate-barium titanate, and potassium bismuth titanate-barium titanate. The term "main component" refers to a material whose main component is one of these compositions. The term "main component" refers to a material whose weight fraction is greater than 10%.
[0062] Furthermore, piezoelectric materials containing these compositions as main components or in combination can be used for the vibration actuator 100 of the present invention.
[0063] From the viewpoint of excellent temperature dependency of the piezoelectric characteristics within the operating temperature range and being able to balance the piezoelectric constant and mechanical quality factor of the piezoelectric material, the following materials are more preferable: namely, materials that are mainly composed of barium calcium zirconate titanate ((Ba,Ca)(Ti,Zr)O3) and sodium niobate-barium titanate (NaNbO3-BaTiO3).
[0064] It is preferable that the main component of the piezoelectric material is barium calcium zirconate titanate (hereinafter referred to as BCTZ). When BCTZ is the main component, the piezoelectricity of BCTZ can be adjusted according to the application by adjusting the amount of Ca and Zr. In addition, the amount of expensive niobium used can be reduced.
[0065] The piezoelectric material is a piezoelectric material containing an oxide having a perovskite structure containing Ba, Ca, Ti, and Zr, and Mn, x, which is a molar ratio of Ca to the sum of Ba and Ca, is 0.02≦x≦0.30, and y, which is a molar ratio of Zr to the sum of Ti and Zr, is 0.020≦y≦0.095 and y≦x; It is preferable that α, which is the ratio of the molar amounts of Ba and Ca to the molar amounts of Ti and Zr, is 0.9955≦α≦1.01, and the Mn content per 100 parts by weight of the oxide is 0.02 to 1.0 parts by weight in terms of metal.
[0066] Such a piezoelectric material can be expressed by the following general formula (1). (Ba 1-x Ca x ) α (Ti 1-y Zr y )O3(1) however, 0.986≦α≦1.100, 0.02≦x≦0.30, 0.02≦y≦0.095 and the content of metal components other than the main component contained in the piezoelectric material is preferably 1 part by weight or less in terms of metal per 100 parts by weight of the metal oxide.
[0067] In particular, it is preferable that the metal oxide contains Mn, and the content of Mn is 0.02 parts by weight or more and 0.40 parts by weight or less in terms of metal per 100 parts by weight of the metal oxide. When Mn is contained within this range, the insulating property and the mechanical quality factor Qm are improved. Here, the mechanical quality factor Qm is a coefficient that represents the elastic loss due to vibration when the piezoelectric material is evaluated as a vibrator, and the magnitude of the mechanical quality factor is observed as the sharpness of the resonance curve in impedance measurement. In other words, it is a constant that represents the sharpness of the resonance of the vibrator. When the mechanical quality factor Qm is large, the amount of distortion of the piezoelectric material becomes larger near the resonance frequency, and the piezoelectric material can be vibrated effectively.
[0068] The metal oxide represented by the general formula (1) means that the metal elements located at the A site of the perovskite structure are Ba and Ca, and the metal elements located at the B site are Ti and Zr. However, some of the Ba and Ca may be located at the B site. Similarly, some of the Ti and Zr may be located at the A site.
[0069] In general formula (1), the molar ratio of the B site element to the O element is 1:3. However, even if the molar ratio is slightly different, it is within the scope of the present invention as long as the metal oxide has a perovskite structure as the main phase.
[0070] Whether a metal oxide has a perovskite structure can be determined, for example, by structural analysis using X-ray diffraction or electron beam diffraction.
[0071] In the general formula (1), x, which indicates the molar ratio of Ca in the A site, is in the range of 0.02≦x≦0.30. When a part of Ba in perovskite-type barium titanate is replaced with Ca within the range, the phase transition temperature between the orthorhombic and tetragonal crystals shifts to the lower temperature side, so that stable piezoelectric vibration can be obtained in the driving temperature range of the vibration actuator. However, if x is larger than 0.30, the piezoelectric constant of the piezoelectric material becomes insufficient, and the performance of the vibration actuator may be insufficient. On the other hand, if x is smaller than 0.02, the dielectric loss (tan δ) may increase. If the dielectric loss increases, the heat generated when applying a voltage to the piezoelectric material to drive the vibration actuator may increase, the motor driving efficiency may decrease, and the power consumption may increase.
[0072] In the general formula (1), y, which indicates the molar ratio of Zr in the B site, is in the range of 0.02≦y≦0.1. If y is greater than 0.1, Td becomes low, less than 80° C., and the temperature range in which the vibration actuator can be used becomes less than 80° C., which is undesirable.
[0073] In this specification, Td refers to the lowest temperature at which the piezoelectric constant after heating a piezoelectric material from room temperature to Td one week after polarization treatment and then cooling it back to room temperature decreases by more than 10% compared to the piezoelectric constant before heating.
[0074] In general formula (1), α, which indicates the ratio of the molar amount of Ba and Ca at the A site to the molar amount of Ti and Zr at the B site, is preferably in the range of 0.9955≦α≦1.010. If α is smaller than 0.9955, abnormal grain growth is likely to occur in the crystal grains constituting the piezoelectric material, and the mechanical strength of the piezoelectric material is reduced. On the other hand, if α is larger than 1.010, the piezoelectric material does not become highly densified and the insulation becomes extremely brittle.
[0075] The method for measuring the composition of the piezoelectric material is not particularly limited. Examples of the method include X-ray fluorescence analysis, ICP emission spectrometry, and atomic absorption spectrometry. Regardless of the measurement method used, the weight ratio and composition ratio of each element contained in the piezoelectric material can be calculated.
[0076] The metal equivalent showing the Mn content is calculated by calculating the content of each metal, Ba, Ca, Ti, Zr, and Mn, measured from the piezoelectric material by X-ray fluorescence analysis (XRF), ICP atomic emission spectrometry, atomic absorption spectrometry, etc. From the content, the elements constituting the metal oxide represented by general formula (1) are converted into oxides, and the value is calculated as the ratio of the weight of Mn to the total weight of 100.
[0077] If the Mn content is less than 0.02 parts by weight, the effect of the polarization process required for driving the vibration actuator may be insufficient. On the other hand, if the Mn content is more than 0.40 parts by weight, the piezoelectric properties of the piezoelectric material may be insufficient, or crystals with a hexagonal structure that do not have piezoelectric properties may appear. Mn is not limited to metallic Mn, and it is sufficient that it is contained in the piezoelectric material as a Mn component, and the form of its inclusion does not matter. For example, it may be solid-dissolved in the B site or contained in the grain boundary. A more preferable form of inclusion is solid-dissolved in the B site from the viewpoint of insulation and sintering ease.
[0078] The piezoelectric material preferably contains 0.042 parts by weight or more and 0.850 parts by weight or less of Bi calculated as metal.
[0079] The piezoelectric material may contain 0.85 parts by weight or less of Bi in terms of metal, based on 100 parts by weight of the metal oxide represented by the general formula (1). The content of Bi relative to the metal oxide can be measured, for example, by ICP emission spectroscopy. Bi may be present at the grain boundaries of the ceramic piezoelectric material, or may be dissolved in the perovskite structure of (Ba,Ca)(Ti,Zr)O3. When Bi is present at the grain boundaries, friction between particles is reduced and the mechanical quality factor is increased. On the other hand, when Bi is incorporated into a solid solution that forms a perovskite structure, the phase transition temperature is lowered, so that the temperature dependence of the piezoelectric constant is reduced and the mechanical quality factor is further improved. It is preferable that Bi is incorporated into the solid solution at the A site, because this improves the charge balance with Mn.
[0080] The piezoelectric material may contain components (hereinafter, "auxiliary components") other than the elements contained in the general formula (1) and Mn and Bi, to the extent that the characteristics do not change. The total amount of the auxiliary components is preferably less than 1.2 parts by weight per 100 parts by weight of the metal oxide expressed by the general formula (1). If the amount of the auxiliary components exceeds 1.2 parts by weight, the piezoelectric characteristics and insulating characteristics of the piezoelectric material may be deteriorated. Since non-lead-based piezoelectric materials have a high Young's modulus, they tend to have a higher resonance frequency than lead-based piezoelectric materials. If the resonance frequency is high, the number of vibrations of the vibrator increases, making it sensitive to changes in the vibration damping member placed between the biasing member and the vibrating body. Therefore, in a vibration type actuator using a non-lead-based piezoelectric material, it is preferable to use a foamed material that has excellent long-term stability and changes little.
[0081] It is further preferable that the phase transition temperature is −10° C. or lower, since this provides excellent temperature dependency of the piezoelectric characteristics within the operating temperature range of the vibration actuator (for example, −30° C. to 60° C.).
[0082] The piezoelectric material of the present invention undergoes a successive phase transition from tetragonal to orthorhombic as the temperature is lowered from room temperature. The phase transition temperature referred to in this specification refers to this phase transition. The phase transition temperature is calculated as the temperature at which the dielectric constant is maximized when the dielectric constant is differentiated with respect to the sample temperature by measuring the dielectric constant while changing the temperature. The crystal system can be evaluated by X-ray diffraction, electron beam diffraction, Raman scattering, or the like. The dielectric constant and electromechanical coupling coefficient are maximized and the Young's modulus is minimized near the phase transition temperature. The piezoelectric constant is a function of these three parameters, and shows a maximum value or an inflection point near the phase transition temperature.
[0083] (Method of manufacturing vibration type actuator) The vibration actuator of the present invention is manufactured by the following manufacturing method. First, a foamed material containing silicone rubber and having bubbles with an average equivalent circular diameter of more than 120 μm is subjected to a pressure and heat treatment to obtain a foamed member. Next, an elastic body and an electromechanical energy conversion element are brought into contact to obtain a vibrating body, and a contact body is prepared. Finally, the vibrating body is biased against the contact body via the foamed member to obtain a vibration actuator. The pressure and heat treatment is performed at a pressure of 600 g / cm. 2 More than 700g / cm 2 This involves holding the foamed material at a temperature of 60°C or more and 80°C or less under pressure as follows:
[0084] (electronic equipment) The electronic device of the present invention is characterized by comprising the vibration actuator of the present invention, a member connected to the contact body of the vibration actuator, and a member position detection means (e.g., an encoder). The electronic device detects the position of the member and operates the vibration actuator until the member reaches a target position, thereby enabling precise control of the position of the member.
[0085] (optical equipment) The optical device of the present invention is characterized by comprising the electronic device of the present invention and at least one of an optical element and an imaging element. FIG. 8 is a schematic diagram showing an embodiment of the optical device of the present invention (focus lens section of a lens barrel device). In FIG. 8, a vibrator 110 having a rectangular piezoelectric material is in pressure contact with a contact body (slider) 104 in the same manner as in FIG. 1(d). A power supply member 507 is connected to the surface side having the first and second regions. When a desired voltage is applied to the vibrator 110 via the power supply member 507 by a voltage input means (not shown), an elliptical motion is generated in the protrusion of the elastic body (not shown). The holding member 501 is joined to the vibrator 110 and is configured not to generate unnecessary vibration. The moving housing 502 is fixed to the holding member 501 with a screw 503 and is integrated with the vibrator 110. The electronic device of the present invention is formed by these members. By attaching the moving housing 502 to the guide member 504, the electronic device of the present invention can move linearly in both directions (forward and reverse directions) along the guide member 504.
[0086] Next, a lens 506 (optical member) that plays the role of a focus lens of the lens barrel device will be described. The lens 506 is fixed to a lens holding member 505, and has an optical axis (not shown) parallel to the moving direction of the vibration actuator. The lens holding member 505, like the vibration actuator, moves linearly on two guide members 504 described later to perform focal position adjustment (focusing operation). The two guide members 504 are members that engage the movable housing 502 and the lens holding member 505, enabling the movable housing 502 and the lens holding member 505 to move linearly. With this configuration, the movable housing 502 and the lens holding member 505 can move linearly on the guide members 504.
[0087] Furthermore, the connecting member 510 is a member that transmits the driving force generated by the vibration actuator to the lens holding member 505, and is fitted and attached to the lens holding member 505. This allows the lens holding member 505 to move smoothly in both directions along the two guide members 504 together with the movable housing 502.
[0088] Further, sensor 508 is provided to detect the position of lens holding member 505 on guide member 504 by reading position information from scale 509 affixed to the side surface of lens holding member 505. As described above, the focus lens unit of the lens barrel device is configured by incorporating the above-mentioned respective members.
[0089] In the above, a lens barrel device for a single-lens reflex camera has been described as an example of an optical device, but the present invention can be applied to a variety of optical devices equipped with a vibration actuator regardless of the type of camera, such as a compact camera in which the lens and camera body are integrated, or an electronic still camera.
[0090] As another configuration of the vibration type actuator, a plurality of vibrators may be in contact with one common contact body, and the contact body may be arranged so that the vibration of the plurality of vibrators causes relative movement of the plurality of vibrators.
[0091] Furthermore, the vibration actuator of the present invention can be applied to medical or engineering fields. Specifically, a wire-driven actuator can be configured that includes a thin member, a wire that is inserted through the thin member and fixed to a part of the thin member, and the vibration actuator described above that drives the wire, and that bends the thin member by driving the wire.
[0092] [Example] Next, the vibration actuator and vibrator of the present invention will be described with reference to examples, but the present invention is not limited to the following examples.
[0093] Example 1 The metal oxide powder was sintered at 1340° C. to obtain a piezoelectric material shown in manufacturing composition 1 in Table 2.
[0094] Production composition 1 is a composition represented by general formula (1), and the values of x, y, and α shown in Table 2 correspond to the respective values in the above-mentioned general formula (1).
[0095] The obtained piezoelectric material was ground and polished to a thickness of 0.5 mm, and then machined into a circular ring having an outer diameter of 62 mm and an inner diameter of 54 mm. The driving phase electrode 101e and the non-driving phase electrode 101f shown in Fig. 1(c) were formed on one side of the shaped piezoelectric material 102. The electrodes were formed by applying silver paste to the piezoelectric material 102 by screen printing, drying, and baking.
[0096] Next, adhesive was applied to elastic body 103 made of SUS420J2, and it was pressed onto piezoelectric material 102 on which electrodes were formed. The circular piezoelectric material and the circular elastic body were positioned using a positioning jig so that the centers of their circles were aligned. Next, heat treatment was performed to harden the adhesive. The piezoelectric material with the elastic body pressed onto it was heated to a temperature T1 = 160°C and held for 180 seconds, then cooled to room temperature, and the pressure was released to obtain a vibrator. Next, an FPC coated with ACP was thermocompression bonded to the electrodes on the piezoelectric material. The thermocompression bonding conditions were temperature T2 = 140°C and holding time of 20 seconds.
[0097] Then, the elastic body SUS420J2 was grounded, and voltages of different polarities were applied alternately to adjacent driving phase electrodes 101e to perform polarization processing. In the polarization processing, multiple external electrodes connected to a power source were brought into contact with the electrodes to be used as sensors among the driving phase electrodes 101e and the driven phase electrodes 101f. After that, the electrodes were heated to T3=100°C, and an electric field equivalent to 2 kV / mm was applied for 30 minutes. After that, the electrodes were cooled to 40°C over 40 minutes while the electric field was still applied, and the voltage application was terminated.
[0098] After that, the first electrode 101a and the second electrode 101b were printed and dried to obtain a vibrator. In the drying process, the temperature of the piezoelectric material was kept below 80°C to prevent depolarization of the piezoelectric material. The obtained vibrator was pressed into contact with a contact body (rotor) made of SUS420J2 to produce a vibration type actuator. The type of foamed material containing siloxane bonds (Si-O-Si) consisting of silicon and oxygen, which was placed between the electro-mechanical energy conversion element and the biasing member, is shown in Example 1 of Table 1. The number N of Q units of silicon contained in the foamed material Q Number of D units in N D Ratio to N Q / ND was 0.23.
[0099] Example 2 A piezoelectric material according to manufacturing composition 1 was obtained in the same manner as in Example 1. The obtained piezoelectric material was ground and polished to a thickness of 0.35 mm, and then processed into a rectangle of 8.9 x 5.7 mm. The first to third electrodes shown in FIG. 3 were formed on both sides of the shaped piezoelectric material in the same manner as in Example 1.
[0100] Next, adhesive was applied to an elastic body made of SUS420J2, and it was pressed against the rectangular piezoelectric material on which the electrodes were formed. The elastic body used had a rectangular section of 9.1 x 5.8 mm, which was larger than the piezoelectric material, and the thickness of the elastic body was between 0.25 and 0.30 mm. The rectangular piezoelectric material and the elastic body were positioned using a positioning jig so that the centers of the rectangular sections were aligned and the sides of the rectangular sections were parallel. In the pressed state, the piezoelectric material was heated to a temperature T1 = 160°C and held for 180 seconds, then cooled to room temperature, and the pressure was released to obtain a vibrator.
[0101] Next, the FPC coated with ACP and the piezoelectric material were pressed together for 20 seconds using a soldering iron at a temperature T2 of 140° C., and the FPC was thermally pressed onto the electrodes provided on the piezoelectric material.
[0102] Next, the piezoelectric material was subjected to a polarization treatment. In the polarization treatment, the elastic body was grounded, and the external electrodes connected to the power source were brought into contact with the first and second electrodes, respectively. The first and second electrodes were already connected to an FPC, but the entirety of the electrodes was not covered by the FPC, and the external electrodes for polarization treatment were brought into contact with the exposed parts. After that, the material was heated to T3=100°C, and an electric field equivalent to 2 kV / mm was applied for 30 minutes, and then the material was cooled to 40°C for 40 minutes while the electric field was still applied, and then the voltage application was terminated. The vibrator obtained by the above process was pressed into contact with a contact body (slider) made of SUS420J2 to produce a vibration type actuator. The type of foamed material containing a siloxane bond (Si-O-Si) consisting of silicon and oxygen, which was placed between the electro-mechanical energy conversion element and the biasing member, is shown in Example 2 of Table 1.
[0103] [Table 1]
[0104] (Examples 3 to 6) The vibration actuators of Examples 3 to 6 were produced in the same manner as in Example 2, except that the type of foam material containing a siloxane bond (Si-O-Si) consisting of silicon and oxygen, which was placed between the electromechanical energy conversion element and the biasing member, was as shown in Table 1.
[0105] Comparative Example 1 A vibration actuator was produced in the same manner as in Example 1, except that felt was placed between the electromechanical energy conversion element and the biasing member.
[0106] Comparative Example 2 A vibration actuator was produced in the same manner as in Example 2, except that felt was placed between the electromechanical energy conversion element and the biasing member.
[0107] (Method of evaluating vibration type actuators) A drive test was performed on the vibration actuators of each of the examples and comparative examples by applying an alternating voltage with an amplitude of 130 Vpp to the first and second electrodes, with the phase difference between the voltages of the first and second electrodes being -90° and 90°.
[0108] When the frequency of the AC voltage is swept from a frequency higher than the resonance frequency of vibration mode A and vibration mode B toward the resonance frequency, the contact body is driven in a direction according to the phase difference of the AC voltage and stops after reaching the maximum speed. For convenience, the directions of movement when the phase difference is -90° and 90° are called the reverse direction and forward direction, respectively. The maximum speed of the vibrator and the frequency at which the maximum speed was reached were measured with a sensor. The power (rated power) at a rated speed lower than the maximum speed was calculated from the current flowing through the drive circuit. Figure 9 shows an example of the measurement results of speed and power versus frequency. Measurements of the maximum speed and rated power were carried out in an environmental atmosphere at 20°C, and the average values for the reverse direction and forward direction were calculated.
[0109] The change in the maximum speed and the change in the rated power of Example 1 were calculated with respect to the maximum speed of the vibration actuator produced in Comparative Example 1. Similarly, the change in the maximum speed and the change in the rated power of Examples 3 to 6 were calculated with respect to the maximum speed of the vibration actuator produced in Comparative Example 2. The results are shown in Table 1.
[0110] In comparison with the vibration actuators of Comparative Example 1 and Comparative Example 2, which used felt, the maximum speed increased and the rated power decreased in Examples 1 and 2, which used foam material A containing a siloxane bond (Si-O-Si) consisting of silicon and oxygen.
[0111] As shown in Example 3, it was also confirmed that the maximum speed increased and the rated power decreased at each temperature in the foamed material B.
[0112] In the foam material C and the foam material D shown in Examples 4 and 5, the maximum speed was equivalent to that of the comparative example, but the rated power was lower.
[0113] In the foam member E shown in Example 6, the maximum speed and rated power were equivalent to those of the felt of Comparative Example 2.
[0114] Example 7 The vibration actuator produced in Example 2 was mechanically connected to an optical member to produce the optical device shown in Figure 8. By controlling the alternating voltage applied to the piezoelectric material based on the position information given to the encoder consisting of a sensor and a scale, it was possible to precisely drive the vibration actuator and the optical member connected to the vibration actuator to the target position. In this optical device, an optical lens was connected to the vibration actuator, and it was confirmed that it had an autofocus function.
[0115] Although the above describes the example of manufacturing composition 1, it was confirmed that the driving characteristics of the vibration actuator of the present invention using manufacturing compositions 2 to 46 and lead zirconate titanate (PZT) were equal to or better than those of felt, as in Example 2.
[0116] As described above, a foam member is provided between the biasing member and the vibrating body, and the number N of Q units of silicon contained in the foam member is Q Number of D units in N D Ratio to N Q / N D It has been found that it is preferable that the value of the resistance be 0.09 or more. By configuring in this manner, it is possible to provide a vibration actuator that is stable over a long period of time and has improved drive characteristics.
[0117] [Table 2]
[0118] The disclosure of this embodiment includes the following configurations and methods.
[0119] (Configuration 1) a vibrating body having an elastic body including an electromechanical energy conversion element and a plate portion and a protrusion portion protruding in the same direction outside the surface of the plate portion; a contact body that comes into contact with the protrusion of the vibrating body and moves relatively to the vibrating body; A foam member in contact with the vibrator; a biasing member that biases the vibration body to the contact body via the foam member, The foam member contains a siloxane bond (Si-O-Si) consisting of silicon and oxygen, The number N of Q units of silicon contained in the foam material Q Number of D units in N D Ratio to N Q / N D A vibration actuator, characterized in that:
[0120] (Configuration 2) 2. The vibration actuator according to claim 1, wherein the foam member is a sponge containing silicone rubber.
[0121] (Configuration 3) 3. The vibration actuator according to claim 1 or 2, wherein the foamed material has bubbles having an average equivalent circle diameter of more than 120 μm.
[0122] (Configuration 4) The electromechanical energy conversion element includes a piezoelectric material and an electrode. 4. The vibration actuator according to any one of claims 1 to 3, wherein the piezoelectric material has a lead content of 1000 ppm or less.
[0123] (Configuration 5) 5. The vibration actuator according to any one of configurations 1 to 4, wherein the plate portion is rectangular.
[0124] (Configuration 6) 6. The vibration actuator according to any one of configurations 1 to 5, wherein the elastic body has two protrusions.
[0125] (Configuration 7) 7. The vibration actuator according to any one of configurations 1 to 6, wherein the foam member is smaller than the electromechanical energy conversion element.
[0126] (Configuration 8) 8. The vibration actuator according to any one of configurations 1 to 7, wherein the foam member is smaller than the elastic body.
[0127] (Configuration 9) 9. The vibration actuator according to any one of configurations 1 to 8, wherein the main component of the electromechanical energy conversion element is a barium titanate system.
[0128] (Configuration 10) 10. The vibration actuator according to any one of configurations 1 to 9, wherein a main component of the electromechanical energy conversion element is barium calcium titanate zirconate.
[0129] (Configuration 11) The material, 11. An electronic device comprising the vibration actuator according to any one of configurations 1 to 10 provided on the member.
[0130] (Configuration 12) At least one of an optical element and an imaging element; 12. An optical device comprising the vibration actuator according to any one of configurations 1 to 11 provided on at least one of the optical devices.
[0131] (Method 1) a step of subjecting a foamed material containing silicone rubber and having bubbles with an average equivalent circular diameter of more than 120 μm to a pressurized heat treatment to obtain a foamed member; A step of contacting an elastic body and an electromechanical energy conversion element to obtain a vibrating body; providing a contact body; a step of biasing the vibrator to the contact body via the foam member to obtain a vibration type actuator; 2. A method for producing a vibration actuator comprising the steps of:
[0132] (Method 2) The pressure and heat treatment is performed at 600 g / cm 2 More than 700g / cm 2 The method for producing the vibration actuator according to method 1, further comprising the step of: maintaining the foamed material at a temperature of 60° C. or more and 80° C. or less under the following pressure. [Explanation of symbols]
[0133] 100 Vibration Actuator 101 Electrode 101a 1st electrode 101b 2nd electrode 101c 3rd electrode 101d 4th electrode 101e Driving phase electrode 101f Non-driven phase electrode 102 Piezoelectric Materials 103 Elastic Body 104 Contact body 106 Protrusion 107 Support part 108 Board part 110 Vibration Body 120 Electromechanical Energy Conversion Devices 121 Pressing member 122 Foam materials 133 Bubbles 134 Skin Layer 501 Retaining member 502 Mobile enclosure 503 Bis 504 Guide member 505 Lens holding member 506 Lens 507 Power Supply Materials 508 Sensors 509 Scale 510 Connecting members
Claims
1. a vibrating body having an elastic body including an electromechanical energy conversion element and a plate portion and a protrusion portion protruding in the same direction outside the surface of the plate portion; a contact body that comes into contact with the protrusion of the vibrating body and moves relatively to the vibrating body; A foam member in contact with the vibrator; a biasing member that biases the vibration body to the contact body via the foam member, The foamed material contains a siloxane bond (Si—O—Si) consisting of silicon and oxygen, The number N of Q units of silicon contained in the foam material Q Number of D units N D Ratio to N Q / N D A vibration actuator, characterized in that:
2. 2. The vibration actuator according to claim 1, wherein the foam member is a sponge containing silicone rubber.
3. 3. The vibration actuator according to claim 1, wherein the foamed material has bubbles having an average equivalent circle diameter of more than 120 [mu]m.
4. The electromechanical energy conversion element includes a piezoelectric material and an electrode.
3. The vibration actuator according to claim 1, wherein the piezoelectric material has a lead content of 1000 ppm or less.
5. 3. The vibration actuator according to claim 1, wherein the plate portion is rectangular.
6. 3. The vibration actuator according to claim 1, wherein the elastic body has two protrusions.
7. 3. The vibration actuator according to claim 1, wherein the foam member is smaller than the electromechanical energy conversion element.
8. 3. The vibration actuator according to claim 1, wherein the foam member is smaller than the elastic body.
9. 3. The vibration actuator according to claim 1, wherein the main component of the electromechanical energy conversion element is a barium titanate system.
10. 3. The vibration actuator according to claim 1, wherein the main component of the electromechanical energy conversion element is barium calcium titanate zirconate.
11. The material, 3. An electronic device comprising the vibration actuator according to claim 1 or 2, which is provided on the member.
12. At least one of an optical element and an imaging element; 3. An optical device comprising the vibration actuator according to claim 1 or 2, which is provided on at least one of the first and second surfaces.
13. a step of subjecting a foamed material containing silicone rubber and having bubbles with an average equivalent circular diameter of more than 120 μm to a pressure and heat treatment to obtain a foamed member; A step of contacting an elastic body and an electromechanical energy conversion element to obtain a vibrating body; providing a contact body; a step of biasing the vibrator to the contact body via the foam member to obtain a vibration type actuator; 2. A method for producing a vibration actuator comprising the steps of:
14. The pressure and heat treatment is performed at 600 g / cm 2 More than 700g / cm 2 14. The method for producing a vibration actuator according to claim 13, further comprising the step of: holding the foaming material at a temperature of 60° C. or more and 80° C. or less under the following pressure:
Citation Information
Patent Citations
Oscillation wave motor
JP1991289371A
Vibration type actuator
JP2022083146A
